2009
DOI: 10.1128/aac.01087-08
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Oxidative Damage to Antimicrobial Lethality

Abstract: A potential pathway linking hydroxyl radicals to antimicrobial lethality was examined by using mutational and chemical perturbations of Escherichia coli. Deficiencies of sodA or sodB had no effect on norfloxacin lethality; however, the absence of both genes together reduced lethal activity, consistent with rapid conversion of excessive superoxide to hydrogen peroxide contributing to quinolone lethality. Norfloxacin was more lethal with a mutant deficient in katG than with its isogenic parent, suggesting that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
202
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(229 citation statements)
references
References 31 publications
24
202
1
2
Order By: Relevance
“…S8A) (66). These results complement independent observations by others that deficiencies in KatG or AhpC increase killing by ampicillin, kanamycin, and norfloxacin (15).…”
Section: Resultssupporting
confidence: 87%
“…S8A) (66). These results complement independent observations by others that deficiencies in KatG or AhpC increase killing by ampicillin, kanamycin, and norfloxacin (15).…”
Section: Resultssupporting
confidence: 87%
“…Since the pknB mutant did not exhibit any gross morphological defects in the cell wall that may have been the underlying cause of its hypersusceptibility toward ␤-lactams, we next sought alternative explanations for the observed phenotype. Recent literature has demonstrated that bactericidal antibiotics, such as ␤-lactams, exert their killing effects through the production of reactive oxygen species (29). Thus, we investigated the potential involvement of the kinase in the stress response by examining the activity of its primary mediator, the alternative sigma factor SigB, in the pknB mutant.…”
Section: Resultsmentioning
confidence: 99%
“…There is a growing body of evidence demonstrating the important role that ROS play in bactericidal antibiotic-mediated killing (24)(25)(26). This understanding of how bactericidal antibiotics result in cell death raises the hypothesis that drug tolerance may be mediated by increased abilities within a cell to detoxify ROS.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate that bactericidal antibiotics with a variety of different mechanisms of action increase ROS production within cells via the Fenton reaction (24)(25)(26)(27). Numerous ROS, and in particular hydroxyl radicals, are toxic to cells and can result in cell death.…”
mentioning
confidence: 86%